2020
DOI: 10.1038/s41598-020-79278-y
|View full text |Cite|
|
Sign up to set email alerts
|

Bone marrow stromal cell therapy improves survival after radiation injury but does not restore endogenous hematopoiesis

Abstract: The only available option to treat radiation-induced hematopoietic syndrome is allogeneic hematopoietic cell transplantation, a therapy unavailable to many patients undergoing treatment for malignancy, which would also be infeasible in a radiological disaster. Stromal cells serve as critical components of the hematopoietic stem cell niche and are thought to protect hematopoietic cells under stress. Prior studies that have transplanted mesenchymal stromal cells (MSCs) without co-administration of a hematopoieti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 59 publications
1
17
0
Order By: Relevance
“…Arsenic can target several sites on hypothalamus-pituitary-interrenal axis which might be the reason for increased cortisol secretion in this study. Arsenic can alter the ACTH and effect blood cortisol levels in fish 3 , 35 , 72 . In the current study, the cortisol was remarkably reduced with combinatorial mixture of Se-NPs and EPA + DHA at 0.4 and 0.2% diet.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Arsenic can target several sites on hypothalamus-pituitary-interrenal axis which might be the reason for increased cortisol secretion in this study. Arsenic can alter the ACTH and effect blood cortisol levels in fish 3 , 35 , 72 . In the current study, the cortisol was remarkably reduced with combinatorial mixture of Se-NPs and EPA + DHA at 0.4 and 0.2% diet.…”
Section: Discussionmentioning
confidence: 99%
“…Se-NPs have essential role in passing the signal from peptides to antigen cells and have their own function such as seleno-methionine. It has role in regulation of HSP during stress condition 4 , 35 . Data from present study suggested that Se-NPs and EPA + DHA at 0.4 or 0.2% might also be helping in synthesis for maintenance of the cellular homeostasis through correct folding of nascent and stress-accumulated misfolded proteins in the cell 82 , 83 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PLX-R18 is given intramuscularly to subjects who got exposure or suspected exposure of IR of ≥ 1 Gy based on Radiation Emergency Medical Management guidelines (NCT03797040). Preclinical studies have shown that xenogeneic, syngeneic or allogeneic MSCs can protect animals from lethal IR injury from ARS by ameliorating damage to the GI tract, CNS, and lungs ( 41 53 ). Our results demonstrate that IFNγ licensed allogeneic MSCs mitigate dosimetry grade ARS lethality.…”
Section: Discussionmentioning
confidence: 99%